2015
DOI: 10.4236/as.2015.611124
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Water Productivity of Chickpea (<i>Cicer arietinum</i> L.) as Influenced by Different Irrigation Regimes and Varieties under Semi Desert Climatic Conditions of Sudan

Abstract: A field experiment was conducted at Hudeiba Research Station Farm, located at Ed-Damer, Sudan during 2011/2012 and 2012/2013 winter seasons to investigate the effect of different irrigation regimes and varieties on chickpea (Cicer arietinum L.) yield, yield components and water productivity. The treatments include three irrigation regimes; irrigation every 10 days (I 1 = full irrigation), irrigation every 15 days (I 2 = moderate stress) and irrigation every 20 days (I 3 = severe stress) and two varieties (Borg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
2
2
0
Order By: Relevance
“…The highest number of pods per plant was observed in 10 days intervals in Atmore (late flowering) than Wad Hamid and Shendi (early flowering). Similar results were reported by (AllaJabow, et. al., 2015).…”
Section: International Journal Of Agricultural and Applied Sciences 1(1)supporting
confidence: 92%
See 1 more Smart Citation
“…The highest number of pods per plant was observed in 10 days intervals in Atmore (late flowering) than Wad Hamid and Shendi (early flowering). Similar results were reported by (AllaJabow, et. al., 2015).…”
Section: International Journal Of Agricultural and Applied Sciences 1(1)supporting
confidence: 92%
“…And this perhaps referred to the role of water stress in old leaves, which will lead to shedding and resulting to reduce the total number of leaves. (AllaJabow, et. al., 2015) they found that the effect of water stress coincides with various growth stage such as germination; seedling and shoot length.…”
Section: Resultsmentioning
confidence: 99%
“…Such trend is mainly due to the differences in climatic conditions and sowing date between both seasons of study. Similar conclusion was reached by Mohammad (2014), Moursi et al (2014) and Jabow et al (2015). Appropriate frequency of irrigation can be determined from the available soil moisture retaining capacity and the rate of faba bean evapotranspiration taking into consideration that it better replenish the soil moisture when about 50% of the total available soil water is exhausted (Allen et al,1998) With respect to, the effect of applied different concentrations (0.2, 0.1, 0.05 and zero %) of polyvinyl alcohol as soil conditioner on total mean actual faba bean evapotranspiration (ETa) results illustrated in Table 3& Table 4 and Figure1.…”
Section: Water Relations Of Faba Bean Crop: Faba Bean Actual Evaopotranspiration (Eta) Affected By Different Water Regimes and Poly Vinylsupporting
confidence: 87%
“…The farmers practice (CB7) recorded the lowest WP of 0.30 kg/ m 3 . Interestingly Jabow et al (2015) observed that in desert conditions of Sudan, chickpea crop exhibited higher water productivity when the interval of irrigation was 15 days as compared to 10 days.…”
Section: Number Of Pods Per Plant (-)mentioning
confidence: 99%